RELATIONSHIP BETWEEN PARENTING PATTERNS AND FOOD INTAKE WITH THE INCIDENCE OF WASTING IN TODDLERS IN THE WORK AREA OF PADANG RUBEK COMMUNITY HEALTH CENTER - Lestari Nadiah; Marniati; Rinawati (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Wasting is one of the indicators of nutrutional status in children. Wasting or thin toddlers is a combination of the trms wasted and severe wasted which is based on the weight index according to height (BB/TB) with a treshold (Z-score) <-2 SD. Based on the table, the study is the high number of wasting toddlers in the padang rubek health center work area in the last 3 years, namely in 2022, wasting toddlers reached 20 people (8,4%). In 2023, the number of wasting toddlers reached 24 people (8,8%) and inceased again in 2024 to 35 people (10,7%), this is figure is considered high because based on the WHO target the wasting figure is <5%. The purpose of this study was to analyze the relationship between maternal parenting patterns and food itake with the incidence of wasting in toddlers in the padang rubek health center work area. The research design used was cross-sectional. The number of samples was 35 people. This study focuses children under five years of age who are malnourished at the padang rubek community health center. Data analysis used the Chi-square statistical test, with a signivicant value of 95%. The results of this study indicate that there is a relationship between parenting patterns and wasting events (p = 0.020), there is a relationship between energy intake and wasting events (p = 0.003), and there is a relationship between protein intake and wasting events (p = 0.009). conlusion, there is a relationship between parenting patterns and food intake whit wasting events in toddlers in the padang rubek health center work area. Sugestions are to provide educatio about nutritious food and good parenting patterns to mothers of toddlers.